Hubungan Status Gizi dan Anemia dengan Kejadian Bayi Berat Badan Lahir Rendah (BBLR) pada Ibu Hamil Aterm di UPT. Puskesmas Majasem Kota Cirebon - Diana Mega Utami; Zulkifli Ahmad; Thysa Thysmelia Affandi (Universitas Pahlawan Tuanku Tambusai, 2025)
Low birth weight (LBW) is an important indicator in assessing the health status of mothers and babies. LBW is closely related to nutritional status and anemia during pregnancy, both of which are public health problems in Indonesia. Pregnant women with chronic energy deficiency (CED) and anemia have a higher risk of giving birth to babies with LBW. Aim: To determine the correlation between nutritional status and anemia with the incidence of low birth weight (LBW) in term pregnant women at the Majasem Health Center, Cirebon City. Methods: This study was conducted in May 2025 at the Majasem Health Center, Cirebon City, used an analytical observational design with a cross-sectional approach. A sample of 90 term pregnant women was selected using a purposive sampling technique based on medical record data from November 2023 to October 2024. The analysis was carried out using the Fisher's Exact Test and Prevalence Ratio (PR). Results: Showed that 22.2% of pregnant women experienced CED and 20.0% experienced anemia. As many as 14.4% of babies were born with low birth weight. There is a significant correlation between nutritional status and the incidence of low birth weight babies (p=0.007; PR=5.744), and anemia with the incidence of low birth weight babies (p=0.020; PR=4.643). Conclusion: There is a correlation between nutritional status and anemia with the incidence of low birth weight infant in term pragnency. Pregnant women with CED and anemia have a higher risk of giving birth to low birth weight babies (LBW).